Taman Seri Serdang a clean zone - New Straits Times, Fairuz Mohd Shahar (2012)
IN conjunction with the Clean Zone competition for 2011/2012 session, the Subang Jaya Municipal Council (MPSJ) recently announced Taman Seri Serdang as a Clean Zone area.